Diabetes Self-Management Education and Support Culturally Tailored for African Americans: COVID-19-Related Factors Influencing Restart of the TX STRIDE Study. Issue 4 (August 2021) - Steinhardt, Mary A.; Brown, Sharon A.; Lehrer, H. Matthew; Dubois, Susan K.; Wright, Jaylen I.; Whyne, Erum Z.; Sumlin, Lisa L.; Harrison, Louis; Woo, Jihun
Purpose: The purpose of this substudy was to determine the most acceptable way to restart the Texas Strength Through Resilience in Diabetes Education (TX STRIDE) study safely using remote technologies. Following the emergence of COVID-19, all in-person TX STRIDE intervention and data collection sessions were paused. Methods: Qualitative descriptive methods using telephone interviews were conducted during the research pause. A structured interview guide was developed to facilitate data collection and coding. Forty-seven of 59 Cohort 1 participants were interviewed (mean age = 60.7 years; 79% female; mean time diagnosed with type 2 diabetes = 11 years). Results: Data categories and subcategories were generated from the interview responses and included: personal experiences with COVID-19, effects of COVID-19 on diabetes self-management, psychosocial and financial effects of COVID-19, and recommendations for program restart. Although some participants lacked technological knowledge, they expressed eagerness to learn how to use remote meeting platforms to resume intervention and at-home data-collection sessions. Six months after the in-person intervention was paused, TX STRIDE restarted remotely with data collection and class sessions held via Zoom. A majority of participants (72.9%) transitioned to the virtual platform restart. Conclusions: Qualitative findings guided the appropriate implementation of technology for the study, which facilitated a successful restart. High retention of participants through the study transition provides evidence that participants are invested in learning how to manage their diabetes despite the challenges and distractions imposed by COVID-19.